Pengaruh penggunaan model pembelajaran inkuiri terbimbing terhadap pencapaian kompetensi fisika siswa kelas X SMAN 8 Padang - Viona Zikra Yerman; Ramli Ramli (Universitas Negeri Padang, 2020)
Student’s learning achievement in Physics lesson are not optimal because they are less involved in getting the concept of physics. Besides of that, models are used in learning is still not diverse and teaching materials are not yet fully used. Therefore, researchers use the Guided Inquiry learning model as an alternative to overcome boredom of students in PBM. This research is aimed to determine the effect of Guided Inquiry Learning Model Against the Achievement in 10th Grade Students of SMAN 8 Padang.This research is using a quasi-experimental design with a randomized control group pretest-posttest design. The populations were students in MIPA 1 - MIPA 5 that were taught by the same teacher with the same teaching hours at SMAN 8 Padang and registered in 2019/2020. Researcher used purposive sampling technique. Knowledge and skills competencies were used as a data research. Instrument of this research a written test with multiple choice to measure knowledge competency and a performance assessment sheet to measure skills competency. The data were analyzed by two average similarity tests. The results showed the average value of Physics learning result for knowledge competence in the experimental class is 79.69 while the control class is 76.19. Meanwhile for the skills competence of experimental class is 83.05 and the control class is 77.83. The conclusion of the research is there is a significant influence from the use of the Guided Inquiry learning model towards the achievement of Physics competence in 10th grade students of SMAN 8 Padang.